Determining the effect of high power pulse ultraviolet (UV) radiation on Bacillus anthracis - Chumakov, Volodymyr; Pinchuk, Nataliia; Kharchenko, Oksana; Muraveynik, Vasyl; Ostrizhnyi, Mykhailo; Tsymbalyuk, Vitaliy; Polka, Nadiia; Bolotin, Vitaliy; Kornieikov, Oleksandr; Paliy, Anatoliy (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the high-power UV radiation at different pulses and its effect on Bacillus anthracis spores. The destruction of pathogenic microorganisms at environmental objects is the key to sustainable epizootological well-being. The results of the study show that the effect of powerful pulses on the destruction of pathogenic microorganisms is achieved during a short series and even single exposures. In this case, a pulsed UV sterilizer based on a magnetoplasma compressor with a pulsed ultraviolet flux power of 3.6 MW with a wavelength of 185‒320 nm of ultraviolet radiation was used. The prospects for pulsed sterilization technology have been shown. As a result of laboratory tests, it was established that the elimination degree of spores of the test microorganism Bacillus anthracis CTI, applied to wooden plates, is lg 2.5; applied to plastic plates – lg 3.2, while the degree of death of spores applied to metal plates is lg 4.0. Based on the results, wood and plastic require more attention when choosing disinfection methods due to their lower efficiency in this context. The high resistance of spore microorganisms requires the use of high dose loads to neutralize the anthrax pathogen. The proposed disinfection methodology is relevant and can be used by veterinary medicine laboratories, livestock farms of various forms of ownership, the scientific community, and industrial enterprises manufacturing technological equipment. Further research should be aimed at devising and improving methods for combating pathogenic microorganisms and ensuring sustainable epizootic well-being